2009
DOI: 10.1159/000201570
|View full text |Cite
|
Sign up to set email alerts
|

The p53 Codon 72 Exon 4 BstUI Polymorphism and Endometrial Cancer in Caucasian Women

Abstract: Objectives: Studies on the association between the p53 Arg72Pro polymorphism and endometrial cancer have reported contrasting conclusions. With the exception of Asian subjects, data demonstrating the influence of this polymorphism on endometrial carcinogenesis in other races/ethnic groups, including Caucasians, are scarce. Thus, we aimed to investigate its role in the development of endometrial cancer and its association with prognostic markers. Methods: A case-control study examining the p53 codon 72 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Other genetic studies also confirmed that the Pro/Pro genotype of p53 codon 72 polymorphism may increase the risk of cervical cancer in Japanese populations and p53 gene polymorphisms appear to be related to a higher grade of cervical cancer (Ashton et al, 2009;Nunobiki et al, 2009). However, Zubor et al did not demonstrate any significant association between p53 codon 72 polymorphism and the risk of cervical cancer in Caucasians (Zubor et al, 2009). Therefore, the possible influence of p53 codon 72 polymorphism on p53 production as well as tumor development and progression in cervical cancer is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic studies also confirmed that the Pro/Pro genotype of p53 codon 72 polymorphism may increase the risk of cervical cancer in Japanese populations and p53 gene polymorphisms appear to be related to a higher grade of cervical cancer (Ashton et al, 2009;Nunobiki et al, 2009). However, Zubor et al did not demonstrate any significant association between p53 codon 72 polymorphism and the risk of cervical cancer in Caucasians (Zubor et al, 2009). Therefore, the possible influence of p53 codon 72 polymorphism on p53 production as well as tumor development and progression in cervical cancer is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,23 Arg72Pro polymorphism of TP53 gene appears to be very informative anthropological marker with characteristic ethnic pattern. Arg72Pro substitution has genotype frequencies in Europeans of ~60, 30 and 10 % for Arg/Arg, Arg/Pro and Pro/Pro, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Whereas the Arg72Pro polymorphism is important for the tumor suppressor function of p53/p73 proteins, we investigated the genotypic frequency of p53 codon 72 polymorphism in the healthy Croatian population, and compared the frequencies of Arg/Arg, Arg/Pro and Pro/Pro genotypes, as well as Arg and Pro alleles with the population of other countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Ashton et al (2009) showed that p53 gene polymorphisms appear to be related to a higher grade of EC. However, Zubor et al did not demonstrate any significant association between p53 codon 72 polymorphism and the risk of EC in Caucasian women (Zubor et al, 2009). Therefore, the possible influence of p53 codon 72 polymorphism on p53 production as well as tumor development and progression in EC is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion criteria, only 10 case-control studies (Esteller et al, 1997;Peller et al, 1999;Agorastos et al, 2004;Roh et al, 2004;Niwa et al, 2005;Ueda et al, 2006;Ashton et al, 2009;Nunobiki et al, 2009;Zubor et al, 2009;Ghasemi et al, 2010) with full-text were included in this meta-analysis and 21 studies were excluded. The flow chart for the study selection is summarized in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%